Perkembangan Sensori Motorik Siswa Sekolah Dasar melalui Pelatihan Seni Tari Tradisional - Qudwatullathifah, Ratri Nuryani; Sholeha, Herisa Hardiyanti; Nugraha, Tria Aditia; Ismuwardani, Zakiyah; Azzahra, Julia (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Sensory-motor development is an important aspect in children's growth and development, including the ability to receive, process and respond to various stimuli from the environment. One way that can be used to develop this ability is through dance practice. The aim of this activity is to develop and improve the sensory-motor abilities of elementary school students through traditional dance training. The methods used are training, demonstration and staging methods. Stages of activity results include: (1) introduction to dance and basic movements; (2) basic movement exercises with rhythmic variations; (3) coordination training by adding hand movements and steps; (4) dance exercises involving balance and flexibility movements; (5) practicing expressions according to dance movements; (6) group dance cohesiveness training; (7) repeating dance practice movements; (8) performing the dance that has been learned in front of friends and parents. The conclusion of this activity is that there is development of elementary school students' sensory-motor abilities through traditional dance training.